Geochemical exploration and assessment of environmental impacts in the Portuguese sector of the Iberian Pyrite Belt - Batista, Maria Joao (2020)
ABSTRACT: This work intends to briefly report the history and application of geochemical exploration techniques in the Iberian Pyrite Belt (IPB). The use of geochemistry in IPB for exploration purposes started in 1950s. Together with geophysics, the soil geochemical exploration surveys performed over several decades were responsible for important discoveries such as Carrasco and Feitais ore-bodies. However, the continuous development of analytical methods and the progress in data processing/modelling led to significant changes in the planning of sampling surveys, and their specific objectives, as well as in the accuracy of geochemical anomalies definition and corresponding interpretation. As a consequence, the number of samples involved in each survey was significantly reduced, but the chemical elements analysed with improved detection limits were considerably extended; additionally, geochemical anomalies were better resolved. Notwithstanding this evolution, data obtained in early soil geochemical surveys (notably by the Serviço de Fomento Mineiro) are still useful in the development of preliminary approaches at a regional scale. Over the years, many studies were made for exploration and environmental assessments, the most relevant of them reported in this chapter. Natural distributions of chemical elements were also identified in these studies as background (if pristine conditions are present) or baseline (depending how disturbed is the area covered by the sampling survey) values. Large part of IPB was, and still is, subjected to poly-metallic mineral exploration or mining, being also the focus of environmental evaluation and/or remediation projects on particular areas that, being the target of long-lasting human intervention, represent paradigmatic case-study examples. The exploration and exploitation works carried out by national and foreign private companies were, and still are, very important for innovative achievements in IPB along with copious contributions from the Portuguese R&D public institutions. Presently, LNEG possesses a vast quantity of geochemical data that can be provided for companies that wish to start their activity in the IPB; some of these datasets are compiled to a unique integrative map also presented in this work. Stream-sediments geochemistry, hydrogeochemistry and lithogeochemistry (of outcropping rock and drill-core samples) represent also important sources of geochemical data in regional or detailed studies over specific target areas in the IPB. However, these techniques are beyond the scope of the present paper which aimed at providing a general overview of the importance of soil geochemistry studies in the current knowledge of the IPB.